The study of the factor that causes problems to the credit card holders among the teachers in Kuala Krai / Farhan Akhnan Ibrahim - Ibrahim, Farhan Akhnan (2010)
The objective of this research is to study the factor that causes problems to the credit card holders among the teachers in Kuala Krai. The respondents selected were 90 teachers from three schools in Kuala Krai area. Each school is divided into 30 teachers as a respondent. 36.7% of respondents were male and 63.3% female. Respondents were also grouped under 5 age diifersnces which below 20 years, 21-30 years old, 31-40 years olds4M0 T-si's old and 50 and above. Four independent variables were identified as the factors and all proved having a significant relationship toward factors that causes problems to the credit card holders among the teachers in Kuala Krai. Cronbach’s Alpha coefficient size indicated that all factors were between 0.769 to 0.865 and it show very good and good indicators to this research. All the alternate hypothesis was accepted and the entire objective answered. Majority of the respondents agreed and accepted the over spending is the most factor that causes problem to the credit card holders. Recommendations to all credit card holders in order to avoid the future problems to any credit card holders are awareness choose the Islamic system and good knowledge.